The Role of Supply Chain Integration in Enhancing Supply Chain Resilience: Risk Management Mediation and Regulatory Uncertainty Moderation - Syafa Alya Camila; Dorina Widowati (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of Supply Chain Integration on Supply Chain Resilience with the role of Supply Chain Risk Management mediation and Regulatory Uncertainty moderation in cement manufacturing companies in the Narogong area, Bogor Regency. This study is motivated by increasing business dynamics and regulatory changes affecting industrial stability, while research integrating risk management mediation and moderation of regulatory uncertainty is still limited, especially in the cement sector in Indonesia. Data was collected through a questionnaire using purposive sampling technique and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that: (1) Internal Integration has a positive effect on Supply Chain Resilience, (2) Supplier Integration has a positive effect on Supply Chain Resilience, (3) Customer Integration has a positive effect on Supply Chain Resilience, (4) Supply Chain Risk Management mediates the positive influence of Internal Integration on Supply Chain Resilience, (5) Supply Chain Risk Management mediates the positive influence of Supplier Integration on Supply Chain Resilience, (6) Supply Chain Risk Management mediates the positive influence of Customer Integration on Supply Chain Resilience, (7) Regulatory uncertainty does not negatively moderate the influence of Internal Integration on Supply Chain Resilience, (8) Regulatory uncertainty does not negatively moderate the influence of Supplier Integration on Supply Chain Resilience according to the hypothetical direction proposed, and (9) Regulatory uncertainty negatively moderates the influence of Customer Integration on Supply Chain Resilience Supply Chain Resilience.